Animo Anggota POKDARWIS Desa Jehem Pada Pembelajaran Bahasa Jepang Pariwisata - Pradhana, Ngurah Indra (KIRYOKU, 2024)
One thing that needs to be developed by members of POKDARWIS Jehem Village, Bangli Regency, Bali Province is the ability to serve tourists from Japan. Based on this background, Japanese Tourism language learning was carried out. The activity has been carried out twice, namely on July 26, 2024 and August 13, 2024. The name of the activity is Sakura (One day of gathering together). Each session was attended by around 50 participants. Based on the enthusiasm for the activity, it was grouped quite high. The first evaluation was carried out by means of a test. By giving questions, 93 people were able to correctly answer questions related to greetings and Japanese letters, 75 people were able to write self-introductions in Japanese, the rest still needed improvement in answering. Evaluation of Japanese language training was carried out by distributing questionnaires. The substance of the questions asked included satisfaction after learning Japanese with the results of 2 people saying they were quite satisfied, 77 people saying they were satisfied, and 21 people saying they were very satisfied. Some suggestions were given in the questionnaire, including improving the quality of the videos shown, more in-depth training on pronunciation and memorizing Japanese terms, and further training on the correct use of chopsticks. Practical evaluations include non-test evaluations. Non-test evaluations were conducted on the material on introducing oneself in Japanese and the use of chopsticks by participants. In the practice of introducing oneself, most were able to perform well, but they still seemed embarrassed because they were not yet confident in pronouncing Japanese terms. This was also seen when using chopsticks. Many were still not used to using chopsticks because it was not a habit in everyday life.